Operation Diagram of Circulating Fluidized Beds (CFBs). (2015) - Zhang, H.L.; Degrève, J.; Dewil, R.; Baeyens, J.
Abstract: CFBs are widely used in the chemical, mineral, environmental and energy process industries. Several authors stressed the need for a clear identification of the different operation regimes in the riser of a CFB, to ensure a better comprehension of the hydrodynamic context, and thus better define the operation and design parameters. First approaches to develop a "work map" of the riser operation, were presented by e.g. Grace[1], Yerushalmi and Avidan[2], Bai et al .[3]. It was further developed by Chan et al .[4] and Mahmoudi et al .[5, 6] for both Geldart A- and B-type powders, in terms of the operating gas velocity (U) and the solids circulation flux (G), which jointly delineate different regimes, called respectively Dilute Riser Flow (DRF), Core-Annulus Flow (CAF) (possibly with a bottom Turbulent Fluidized Bed, TFBB), and Dense Riser Upflow (DRU). For a given powder and its associated transport velocity, UTR, the combination of U and G will determine the flow regime encountered. Experiments in CFB risers of 0.05 (2.5 m high), 0.1 and 0.15 m I.D. (both 6.5 m high), have demonstrated that common riser operations can be hampered by a specific (U, G) range where choking occurs. Angular sand, rounded sand, and spent FCC (all A-type powders) were used as bed material. Gas velocities were varied between 2 and 10 m/s, for solids circulation fluxes between 10 and 260 kg/m 2 s. Choking is understood as the phenomenon where a small change in gas or solids flow rate prompts a large change in the pressure drop and/or solids holdup during the gas-solid flow: the stable riser upflow regime is no longer maintained when G-values exceed a certain limit for a given gas velocity. Experimental results were empirically correlated, and proved to be about 30% lower than predicted by the correlation of Bi and Fan[7], but largely exceeding other predictions. Introducing the findings into the available operation diagram [5, 6], adds a region where stable riser operation is impossible. The adapted diagram enables CFB designers to better delineate the operating characteristics.